2016
DOI: 10.1038/bjc.2016.34
|View full text |Cite
|
Sign up to set email alerts
|

Changing molecular profile of brain metastases compared with matched breast primary cancers and impact on clinical outcomes

Abstract: Background:Breast cancer commonly metastasises to the brain, but little is known about changes in the molecular profile of the brain secondaries and impact on clinical outcomes.Methods:Patients with samples from brain metastases and matched breast cancers were included. Immunohistochemical analysis for oestrogen receptor, progesterone receptor, p27kip1, cyclin D1, epidermal growth factor receptor, insulin like growth factor 1, insulin like growth factor 1 receptor, vascular endothelial growth factor A, transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 65 publications
6
17
0
Order By: Relevance
“…Compared to published data, ER loss was more common in our series (NCR 80% vs. 36%), especially as only one of the ER negative patients gained ER expression ( Table V). The data on PgR conversion in the literature are varying widely from 1 conversion in 41 matched pairs (19) to a 25% conversion rate (8) that is very similar to our study. Former studies have shown Her2/neu expression to be more stable than the ER or PgR (22,23).…”
Section: Discussionsupporting
confidence: 85%
“…Compared to published data, ER loss was more common in our series (NCR 80% vs. 36%), especially as only one of the ER negative patients gained ER expression ( Table V). The data on PgR conversion in the literature are varying widely from 1 conversion in 41 matched pairs (19) to a 25% conversion rate (8) that is very similar to our study. Former studies have shown Her2/neu expression to be more stable than the ER or PgR (22,23).…”
Section: Discussionsupporting
confidence: 85%
“…In our series of six HER2-positive breast cancers with brain metastasis, four cases harbored TP53 likely pathogenic mutations private to or enriched in the brain metastases. Indeed, our results here, as well as those from previous studies [ 33 36 ], suggest that breast cancers may undergo clonal shifts and acquire additional somatic genetic alterations in the progression from primary to metachronous brain metastasis after systemic therapy. HER2 amplification as a truncal alteration is likely to be true for the majority of HER2-positive breast cancers.…”
Section: Discussionsupporting
confidence: 83%
“…Duchnowska et al 10 and Thomson et al 11 reported ERBB2/HER2-negative to ERBB2/HER2-positive switching frequencies of 16% and 18% respectively in BrM via IHC. Gutierrez et al 12 reported an ERBB2/HER2-switching frequency of 11% in tamoxifen-resistant tumors, and notably, 6 of 7 cases with ERBB2 / HER2 expression gains were ER-positive.…”
Section: Discussionmentioning
confidence: 99%